G‐Protein coupled receptor 64 promotes invasiveness and metastasis in Ewing sarcomas through PGF and MMP1. Issue 1 (14th March 2013) - Richter, Günther HS; Fasan, Annette; Hauer, Kristina; Grunewald, Thomas GP; Berns, Colette; Rössler, Sabine; Naumann, Ivonne; Staege, Martin S.; Fulda, Simone; Esposito, Irene; Burdach, Stefan
Abstract Metastatic spread in Ewing sarcomas (ES) is frequent and haematogenous. G‐protein coupled receptor 64 (GPR64), an orphan receptor with normal expression restricted to human epididymis is specifically over‐expressed in ES among sarcoma, but also up‐regulated in a number of carcinomas derived from prostate, kidney or lung. Inhibition of GPR64 expression in ES by RNA interference impaired colony formation in vitro and suppressed local tumour growth and metastasis in Rag2−/−γC−/− mice. Microarray analysis after GPR64 knock down revealed a GPR64‐mediated repression of genes involved in neuronal development like SLIT, drosophila, homolog of, 2 (SLIT2), and genes regulating transcription including pre‐B cell leukemia homeobox 2 (PBX2). Concurrently, the suppression of GPR64 increased ES susceptibility to TRAIL induced apoptosis. Moreover, a GPR64‐mediated induction of placental growth factor (PGF) in ES was observed. PGF suppression by RNA interference resulted in a reduction of metastatic growth similar to that observed after GPR64 knock down. Importantly, inhibition of GPR64 as well as PGF expression was associated with a reduced expression of matrix metalloproteinase (MMP) 1 and invasiveness in vitro. Furthermore, MMP1 knock down abrogated lung metastasis in Rag2−/−γC−/− mice. Thus, GPR64 expression in ES maintains an immature phenotype that is less sensitive to TRAIL‐induced apoptosis and via its up‐regulation of PGF and MMP1 orchestrates and promotes invasiveness and metastatic spread. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.